2014
DOI: 10.1155/2014/781683
|View full text |Cite
|
Sign up to set email alerts
|

Aging: A Predisposition to Dry Eyes

Abstract: Dry eye syndrome is a disease of the ocular surface and tear film that is prevalent in older adults. Even though the degree of visual acuity loss in dry eye patients is commonly mild-to-moderate, in the aging population, this minimal change in visual status can lead to a significant decrease in visual function and quality of life. A healthy ocular surface is maintained by appropriate tear production and tear drainage, and deficiencies in this delicate balance can lead to dryness. In the aging eye, risk factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
67
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(79 citation statements)
references
References 76 publications
10
67
0
2
Order By: Relevance
“…In another study conducted by Lokare et al, they found that QOL was significantly better among young people. [4] This finding is corroborated with the finding of a study done by Lahariya et al [5,6] As the age advances, the health related problems become more common to a person. Gradually and gradually the power to work decreases and people are more confined to his/her own house.…”
Section: Discussionsupporting
confidence: 74%
“…In another study conducted by Lokare et al, they found that QOL was significantly better among young people. [4] This finding is corroborated with the finding of a study done by Lahariya et al [5,6] As the age advances, the health related problems become more common to a person. Gradually and gradually the power to work decreases and people are more confined to his/her own house.…”
Section: Discussionsupporting
confidence: 74%
“…Normal tear production creates about 10–15 mm of wetness on each paper strip. Older adult patients may wet only about 10 mm because hypolacrimation occurs with aging (Sharma & Hindman, 2014). A value of less than 5 mm is suggestive of a dry eye state.…”
Section: Management Of Ocular Toxicitymentioning
confidence: 99%
“…Increased osmolarity of the tear film can lead to morphological changes in the cornea and conjunctiva; activation of the inflammatory cascade can induce apoptotic cell death in the corneal epithelium and reduce the number of conjunctival goblet cells [2, 3]. Prevalence of DES increases with age, significantly affecting the quality of life of senior patients [1, 4, 5]. Artificial tear treatment that is typically used to alleviate DES symptoms does not target the cause of the disease.…”
Section: Introductionmentioning
confidence: 99%